Chylothorax Postsophagectomy - Taruselli, Roberto R; Nogues, Cecile; Balboa, Oscar (Cirugía del Uruguay, 2002)
Two patients who suffered esophageal cancer were subject to transhiatal esophagectomy; however they developed chylothorax at postoperative. This was detectad by a leak of chylous /iquid through thoracic drainage tube.